Optimization Design and Application of Niobium‐Based Materials in Electrochemical Energy Storage. Issue 1 (28th October 2020) - Lian, Yue; Yang, Ning; Wang, Dawei; Zheng, Yujing; Ban, Chaolei; Zhao, Jing; Zhang, Huaihao
Abstract : In various energy storage devices, the development and research of electrode materials has always been a key factor. Nb‐based materials are one choice of energy storage materials because of the good ion‐diffusion channels and high theoretical capacity. More importantly, their advantages, such as safe potential range, high structural stability, and highly reversible redox reaction with small strain, are conducive to efficient, safe, and stable energy storage development. Based on aforementioned superiority, much of the research is to further optimize performance of Nb‐based materials by unique nano‐morphology design, lattice regulation, and functional additives composition, showing good electrochemical performance in many kinds of devices. This review mainly introduces the classification of Nb‐based materials used for energy storage, their application in different battery systems, and common optimization methods. Accordingly, the deficiencies and prospects of Nb‐based materials are also discussed in detail. Abstract : Niobium‐based materials show significant advantages and potential in energy storage systems. This paper provides an overview of the types and applications of niobium‐based materials in various systems. In addition, the optimal design of niobium‐based materials is discussed in detail.